2019
DOI: 10.1111/corg.12299
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the role of multiple blockholders: Evidence from closely held firms

Abstract: Research Question/Issue: This paper disentangles how the modes of ownership distribution among multiple blockholders and their heterogeneity shape principalprincipal conflicts and, in turn, affect firm performance. The paper offers empirical evidence from a panel of Italian closely held firms over the period 2009-2014. Research Findings/Insights:We explore the principal-principal conflicts among blockholders across two distinct control structures. When a single blockholder controls the firm, principal-principa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 117 publications
0
9
0
Order By: Relevance
“…Focusing on family firm governance, Chrisman et al (2016) argue that managerial discretion is shaped by “prevailing cultural, political, regulatory, competitive, and capital market conditions” (p. 722). Additionally, the family members’ ability to impose specific heuristics in making strategic decisions depends on factors including the composition of the board of directors (Bettinelli, 2011), the heterogeneity among the largest blockholders (Russino et al, 2019), the implementation of mechanisms to disconnect cash flow and control rights, such as pyramids or loyalty shares. Focusing on family firm resources, the available cash flow and level of indebtedness appear to be respectively a key source and limitation of managerial discretion (Dagnino et al, 2019).…”
Section: A Framework For the Psychological Foundations Of Management mentioning
confidence: 99%
“…Focusing on family firm governance, Chrisman et al (2016) argue that managerial discretion is shaped by “prevailing cultural, political, regulatory, competitive, and capital market conditions” (p. 722). Additionally, the family members’ ability to impose specific heuristics in making strategic decisions depends on factors including the composition of the board of directors (Bettinelli, 2011), the heterogeneity among the largest blockholders (Russino et al, 2019), the implementation of mechanisms to disconnect cash flow and control rights, such as pyramids or loyalty shares. Focusing on family firm resources, the available cash flow and level of indebtedness appear to be respectively a key source and limitation of managerial discretion (Dagnino et al, 2019).…”
Section: A Framework For the Psychological Foundations Of Management mentioning
confidence: 99%
“…The literature on banks' corporate governance is mainly comprised of the assessment of risk-taking and the performance of the banks. Banks' risk-taking comportment varies with the shareholders' discretionary power within the structure of corporate governance of the banks (Laeven & Levine, 2009;Ponomareva et al, 2019;Russino et al, 2019). Moreover, capital reserve requirements and deposit insurance policies depend on the ownership structure of banks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The firms in concentrated ownership are managed by large shareholders and owners and managers are alike hence the problems of the agency are likely to be limited Maheshwari & Gupta (Maheshwari & Gupta, 2018). However, a high concentration of ownership gives discretionary powers to larger shareholders due to which conflict of interest could arise with the minority shareholders (Johnson et al, 2000;Oradi et al, 2020;Russino et al, 2019). The owners of such firms possess rights to influence decisions and affect the operational activities due to equity tunneling i.e.…”
Section: Ownership Structure Specific A) Ownership Concentrationmentioning
confidence: 99%
“…The international scope of corporate governance research is indicated by the diverse set of governance environments studied in recent CGIR articles that include Australia, Canada, China, Germany, India, Indonesia, Iran, Italy, Japan, Korea, Russia, Spain, Sweden, Taiwan, the United Kingdom, the United States, and Vietnam, as well as multicountry studies (e.g., Deloof, Du, & Vanacker, 2020; Desender, LópezPuertas‐Lamy, Pattitoni, & Petracci, 2020; García‐Sánchez & García‐Meca, 2018; Lazzarini & Musacchio, 2018; Qian, Cao, & Cao, 2018; Tribó, 2019; Zhou & Guillén, 2019). Corporate governance research is by no means restricted to the average publicly held corporation but also deals with the unique challenges associated with specific types of firms like, for instance, audit firms (La Rosa, Caserio, & Bernini, 2019), banks (Sheedy & Griffin, 2018), business groups (Shin, Hyun, Oh, & Yang, 2018), closely held firms (Russino, Picone, & Dagnino, 2019), declining firms (Abebe & Tangpong, 2018), entrepreneurial ventures (Pérez‐Calero, Larrañeta, & Wright, 2019), family firms (Yeh & Liao, 2019), foundations (Thomsen, Poulsen, Børsting, & Kuhn, 2018), institutional investors (Semenova & Hassel, 2019), intergovernmental organizations (Federo & Saz‐Carranza, 2018), initial public offerings (IPOs) (González, Guzmán, Tellez‐Falla, & Trujillo, 2019), as well as state‐owned enterprises (Apriliyanti & Randøy, 2019). This research intensity demonstrates the spread of corporate governance studies in multiple disciplines but also leads to higher levels of fragmentation of the field.…”
Section: Introductionmentioning
confidence: 99%
“…. Corporate governance research is by no means restricted to the average publicly held corporation but also deals with the unique challenges associated with specific types of firms like, for instance, audit firms (La Rosa, Caserio, & Bernini, 2019), banks (Sheedy & Griffin, 2018), business groups (Shin, Hyun, Oh, & Yang, 2018), closely held firms (Russino, Picone, & Dagnino, 2019), declining firms (Abebe & Tangpong, 2018), entrepreneurial ventures (Pérez-Calero, Larrañeta, & Wright, 2019), family firms (Yeh & Liao, 2019), foundations (Thomsen, Poulsen, Børsting, & Kuhn, 2018), institutional investors (Semenova & Hassel, 2019), intergovernmental organizations (Federo & Saz-Carranza, 2018), initial public offerings (IPOs) (González, Guzmán, Tellez-Falla, & Trujillo, 2019), as well as state-owned enterprises (Apriliyanti & Randøy, 2019). This research intensity demonstrates the spread of corporate governance studies in multiple disciplines but also leads to higher levels of fragmentation of the field.…”
mentioning
confidence: 99%